Endoscopically Assisted Resection of a Rare Mass: Intra-Articular Osteochondroma of Shoulder Originated from Scapula - Baran Sarikaya; Fatih Suluova; Baki Volkan Cetin; Zeynep Bekin Sarikaya (Case Reports in Orthopedics)
Osteochondromas are the most common benign bone tumors which are mostly seen in the metaphysis of distal femur, proximal tibia, and proximal humerus. As arising from flat bones such as scapula is a rare case, intra-articular osteochondroma is also rare. When the literature is searched it appeared that the scapula and shoulder joint are an uncommon site for osteochondroma. We present a case in which a patient had an osteochondroma placed in shoulder joint and originated from scapula which is a rare situation determined in the literature.